Relationship between Institutional Structure and Economic Growth in Nepal - Duwal, Niroj (Khwopa Journal, 2023)
The macroeconomic performances of any countries are influenced by the with institutional structure. This study aims to estimate the effects of capital formation, labor force participation, and basically institutional index of economic freedom; size of government, legal system and property rights, freedom to trade internationally, sound money and regulation on economic performance using time series data from 2001 to 2020 using ARDL model. The results shows that the gross capital formation, the labor force participation rate have positive relation with GNI per capita whereas the legal system and property rights have negative relation with GNI per capita increases. In long run, only the annual growth of gross capital formation has significant relation with GNI per capita growth but rest of the variables are insignificant. It can be concluded that the institutions are less likely efficient. The bureaucratic quality is least effective, doing business is costly due to weak social structure. The existing institutions have not sufficient level of regulations legally. It can be claimed that there is not efficient set of institutional structure which is valid in every country as a good institution in Nepal.